Composite white film for reducing subfissure rate of battery piece

By adopting a composite white film structure in photovoltaic modules, the low pre-crosslinking and fluidity of the high-permeability EVA layer reduces the cell cracking rate, and the adhesion between the film and the back plate is improved through weak organic acids, the problems of high cracking rate and low peeling force of the cell are solved when the component is laminated, and efficient power generation and reliability of the component are achieved.

CN119709027APending Publication Date: 2025-03-28ZHEJIANG TONY ELECTRONICS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310724792.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-19
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The conventional single-layer white EVA film has a high crack rate when the component is laminated, and the peeling force with the cell and back plate is low, resulting in reduced component power and increased heat spot risk.

Method used

The composite white film structure is adopted, including a highly permeable EVA layer and a white EVA layer, and the cell cracking rate is reduced through the low pre-crosslinking degree and fluidity of the high permeable EVA layer, and the adhesion between the adhesive film and the back plate is improved through organic weak acids.

Benefits of technology

It greatly reduces the hidden crack rate of the battery cell, improves the peel strength of the composite white film and the battery cell and back plate, reduces the risk of outdoor heat spots and delamination of the components, and improves the reliability of the components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119709027A_ABST
    Figure CN119709027A_ABST
Patent Text Reader

Abstract

The invention relates to a composite white film for reducing the subfissure rate of a battery piece for photovoltaic solar packaging, which is formed by integrally co-extruding a two-layer structure and comprises a high-transmittance EVA (Ethylene Vinyl Acetate) layer and a white EVA layer from top to bottom in sequence. The composite white film solves the problems that a conventional single-layer white EVA adhesive film is high in subfissure rate of a battery piece and low in stripping force of the battery piece and a back plate during module lamination, so that the hot spot and delamination risk of the module is reduced, the reliability of the module is improved, the preparation method is simple, the production efficiency is high, the cost is low, and large-scale production can be achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of solar energy encapsulation adhesive films, in particular to a composite white film for reducing the hidden crack rate of solar cells. Background Art

[0002] As the photovoltaic industry continues to pursue cost reduction and technological innovation, various new technologies that can improve the power generation efficiency of modules are emerging. As a simple solution that can significantly increase the power of modules, white EVA film has also been rapidly and widely used on the module side. White EVA film is applied on the back of the module to reflect the unused gap light between the cells and the infrared light that is not absorbed by the cells, prompting the cells to absorb and utilize these two types of light again, thereby increasing the power generation of the module by 5-10W.

[0003] The white EVA film needs to be irradiated with electrons to produce a certain degree of pre-crosslinking, thereby making the EVA resin lose fluidity; to prevent the white EVA resin from flowing to the cell and covering part of the front area of ​​the cell due to the negative pressure of the vacuum laminator and the lamination pressure during the lamination of the components, causing the problem of white overflow and reducing the power of the components. The conventional single-layer white EVA film uses electron irradiation technology, which solves the problem of white overflow, but the pre-crosslinking degree is relatively high and needs to reach 30-45%. When the cell is thicker, the cell size is not large, and the cell spacing is large, the cell crack rate after lamination is low; however, with the advancement of industry technology, in order to further reduce manufacturing costs, reduce the cost per kilowatt-hour, and increase the power generation of components, the industry has entered the era of 182 cells and 210 cells, and further reduced the spacing between cells and the thickness of the cells from 175um to 150um. The higher the pre-crosslinking degree, the harder the EVA resin is, while the lower the fluidity is. The EVA resin cannot fill the gap between the bend of the solder ribbon and the battery cell well. The two conditions make it impossible for the EVA resin to provide a good buffer between the solder ribbon and the battery cell during component lamination, and the micro-crack rate of the battery cell reaches more than 50%. These micro-cracks will be further enlarged when the component production line vibrates, when the component is transported and installed, or when it encounters impacts such as hail during operation, and even evolve into cracks that run through the entire battery cell (such as Figure 1 and Figure 2 ), which in turn reduces the power of the module, increases the risk of hot spots in the module, and threatens the safety of the power station. At the same time, the higher the pre-crosslinking, the worse the fluidity of the EVA resin, the worse the wettability to the glass and backplane, the worse the bonding performance with the glass and backplane, and the higher the risk of delamination of the module outdoors.

[0004] To this end, the industry has developed a double-layer co-extruded white EVA film technology to reduce the problem of micro-cracks in battery cells. The composite white film has a high-transmittance EVA layer on the upper layer, which contacts the battery cell, and a white EVA layer on the lower layer, which contacts the backplane. The high-transmittance EVA layer on the upper layer can alleviate the white overflow of the lower white EVA layer, so that the pre-crosslinking degree can be reduced to between 15-25% (the pre-crosslinking degree of the high-transmittance EVA layer and the white EVA layer is not much different). Although the micro-crack rate of the battery cell has been greatly reduced, it is still 10-20%, and the micro-crack rate is still relatively high. Summary of the invention

[0005] In order to overcome the above problems, a composite white film is provided for reducing the hidden crack rate of battery cells, so as to solve the problems of high hidden crack rate of battery cells and low peeling force between battery cells and back sheets during component lamination of conventional single-layer white EVA adhesive films.

[0006] The technical solution of the present invention is: a composite white film for reducing the hidden crack rate of a battery cell, comprising a high-transmittance EVA layer and a white EVA layer distributed in sequence from top to bottom, wherein:

[0007] The high-transmittance EVA layer comprises, by mass, 100 parts of EVA resin, 1-5 parts of flow enhancer, 0.6 parts of tert-butyl peroxycarbonate-2-ethylhexyl ester, 0.5 parts of triallyl isocyanurate, 0.8 parts of ethoxylated trimethylolpropane triacrylate, 0.3 parts of γ-methacryloxypropyl trimethoxysilane, 0.2 parts of bis(2,2,6,6,-tetramethyl-4-piperidinyl) sebacate, and 0.05 parts of triethylene glycol bis[β-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate];

[0008] The white EVA layer comprises, by mass, 100 parts of EVA resin, 18 parts of EVA masterbatch containing 60% titanium dioxide, 0.65 parts of tert-butyl peroxycarbonate-2-ethylhexyl ester, 0.55 parts of triallyl isocyanurate, 0.85 parts of ethoxylated trimethylolpropane triacrylate, 0.32 parts of γ-methacryloxypropyl trimethoxysilane, 0.3 parts of bis(2,2,6,6,-tetramethyl-4-piperidinyl) sebacate, 0.05 parts of triethylene glycol bis[β-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate], and 0.1-0.3 parts of an organic weak acid.

[0009] Furthermore, the thickness of the high-transmittance EVA layer is 50-150um, and the thickness of the white EVA layer is 300-450um;

[0010] Further, the flow enhancer is a low molecular weight polyolefin containing double bonds;

[0011] Further, the low molecular weight polyolefin containing double bonds includes any one or a combination of at least two of polyisobutylene with a-terminal double bond, polyisoprene containing double bonds and polybutadiene containing double bonds;

[0012] Furthermore, the molecular weight of the low molecular weight polyolefin containing double bonds is 400-1000 g / mol;

[0013] Furthermore, the organic weak acid includes any one or a combination of at least two of lauric acid, myristic acid, palmitic acid and stearic acid;

[0014] Furthermore, the pre-crosslinking degree of the high-transmittance EVA layer is 2-10%;

[0015] Furthermore, the pre-crosslinking degree of the white EVA layer is 20-30%;

[0016] Furthermore, the composite white film is produced by co-extrusion of single-screw twin machines and composite die head, and then through casting, embossing, trimming, winding and irradiation.

[0017] The beneficial effects of the present invention are:

[0018] 1. The high-transmittance EVA layer of the present invention has good fluidity, and can better fill the gap between the welding strip and the battery cell during component lamination, prevent hard contact between the two, and provide a buffering effect. At the same time, after the pre-crosslinking of the high-transmittance EVA layer is reduced, the hardness of the layer is reduced, and the battery cell can be provided with a pressure buffering effect during component lamination. The simultaneous action of the two reasons greatly reduces the hidden crack rate of the battery cell during component lamination, thereby reducing the risk of outdoor hot spots of the component. Since the high-transmittance EVA layer has a lower degree of pre-crosslinking and better fluidity, it has better wettability to the battery cell during component lamination, thereby improving the peeling strength between the composite white film and the battery cell, reducing the risk of component delamination, and improving the reliability of the component. The low molecular weight polyolefin containing double bonds is a transparent liquid, which will not affect the light transmittance of the high-transmittance EVA layer, thereby not reducing the reflectivity of the underlying white EVA layer.

[0019] 2. The lower white EVA layer of the present invention is more difficult to overflow onto the battery cell under the lamination pressure of the component than the single-layer white EVA layer due to the hindering effect of the upper high-transmittance EVA layer. Therefore, the pre-crosslinking degree can be lower than that of the conventional single-layer white EVA, reduced to 20-30%. After the pre-crosslinking is reduced, the fluidity of the adhesive film is better than that of the conventional single-layer white EVA, and the wettability to the backplane is better. At the same time, the organic weak acid can dissociate and release hydrogen ions under the high temperature condition of 140-150°C during component lamination. The hydrogen ions can accelerate the hydrolysis of the silane coupling agent in the adhesive film, quickly produce a large number of hydroxyl groups, and undergo a dehydration condensation reaction with the hydroxyl groups in the inner layer of the backplane, thereby improving the bonding force between the adhesive film and the backplane. Under the action of the above two reasons, the peeling strength between the composite white film and the backplane is improved, the risk of component delamination is reduced, and the reliability of the component is improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 It is a schematic diagram of the composite white film of the present invention;

[0021] Figure 2 This is a schematic diagram of a conventional single-layer white film; DETAILED DESCRIPTION

[0022] The present invention will be further described below with reference to the accompanying drawings by way of embodiments.

[0023] This specific embodiment is merely an explanation of the present invention and is not a limitation of the present invention. After reading this specification, those skilled in the art may make non-creative modifications to the present embodiment as needed. However, as long as they are within the scope of the claims of the present invention, they are protected by the patent law.

[0024] Embodiment 1, as Figure 1 As shown, a composite white film for reducing the hidden crack rate of a battery cell comprises a high-transmittance EVA layer 1 and a white EVA layer 2 which are sequentially arranged from top to bottom, wherein:

[0025] The high-transmittance EVA layer 1 includes, by mass, 100 parts of EVA resin, 1-5 parts of flow enhancer, 0.6 parts of tert-butyl peroxycarbonate-2-ethylhexyl ester, 0.5 parts of triallyl isocyanurate, 0.8 parts of ethoxylated trimethylolpropane triacrylate, 0.3 parts of γ-methacryloxypropyl trimethoxysilane, 0.2 parts of bis(2,2,6,6,-tetramethyl-4-piperidinyl) sebacate, and 0.05 parts of triethylene glycol bis[β-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate];

[0026] The white EVA layer 2 comprises, by mass, 100 parts of EVA resin, 18 parts of EVA masterbatch containing 60% titanium dioxide, 0.65 parts of tert-butyl peroxycarbonate-2-ethylhexyl ester, 0.55 parts of triallyl isocyanurate, 0.85 parts of ethoxylated trimethylolpropane triacrylate, 0.32 parts of γ-methacryloxypropyl trimethoxysilane, 0.3 parts of bis(2,2,6,6,-tetramethyl-4-piperidinyl) sebacate, 0.05 parts of triethylene glycol bis[β-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate], and 0.1-0.3 parts of an organic weak acid.

[0027] The flow enhancer in the high-transmittance EVA layer 1 of the present invention has a double bond, which can absorb and consume the incoming electron beam during irradiation. The double bond and the electron form active carbon free radicals (·CC·), and then the carbon free radicals undergo self-polymerization reaction, resulting in very little cross-linking reaction of the EVA resin, so that the high-transmittance EVA layer 1 has a lower pre-crosslinking degree. Therefore, the high-transmittance EVA layer 1 has good fluidity and can better fill the gap between the welding strip and the battery cell during component lamination to prevent hard contact between the two and provide a buffering effect. At the same time, after the pre-crosslinking of the high-transmittance EVA layer 1 is reduced, the hardness of the layer is reduced, which can provide a pressure buffering effect for the battery cell during component lamination. The simultaneous action of the two reasons greatly reduces the hidden crack rate of the battery cell during component lamination, thereby reducing the risk of outdoor hot spots in the component (the ordinary double-layer co-extruded white film high-transmittance EVA layer on the market does not have this function, so the EVA resin will undergo a higher pre-crosslinking under the action of the electron beam, and the pre-crosslinking degree reaches 15-25%). Since the high-transmittance EVA layer has a lower degree of pre-crosslinking and better fluidity, it has better wettability to the battery cells during component lamination, thereby improving the peel strength between the composite white film and the battery cells, reducing the risk of component delamination, and improving the reliability of the components. The low molecular weight polyolefin containing double bonds is a transparent liquid and will not affect the light transmittance of the high-transmittance EVA layer, thereby not reducing the reflectivity of the underlying white EVA layer.

[0028] The lower white EVA layer 2 of the present invention is more difficult to overflow onto the battery cell under the pressure of the component lamination than the single-layer white EVA layer due to the obstruction of the upper high-transmittance EVA layer 1. Therefore, the pre-crosslinking degree can be lower than that of the conventional single-layer white EVA, reduced to 20-30%. After the pre-crosslinking is reduced, the fluidity of the adhesive film is better than that of the conventional single-layer white EVA, and the wettability to the backplane is better. At the same time, the organic weak acid can dissociate and release hydrogen ions under the high temperature condition of 140-150°C during the component lamination. The hydrogen ions can accelerate the hydrolysis of the silane coupling agent in the adhesive film, quickly produce a large number of hydroxyl groups, and react with the hydroxyl groups in the inner layer of the backplane to undergo a dehydration condensation reaction, thereby improving the bonding force between the adhesive film and the backplane. Under the action of the above two reasons, the peeling strength between the composite white film and the backplane is improved, the risk of component delamination is reduced, and the reliability of the component is improved.

[0029] Preferably, the thickness of the high-transmittance EVA layer 1 is 50-150um, and the thickness of the white EVA layer 2 is 300-450um;

[0030] Preferably, the flow enhancer is a low molecular weight polyolefin containing double bonds, wherein the low molecular weight polyolefin containing double bonds includes any one or a combination of at least two of polyisobutylene with a-terminal double bond, polyisoprene containing double bonds and polybutadiene containing double bonds;

[0031] Preferably, the molecular weight of the low molecular weight polyolefin containing double bonds is 400-1000 g / mol;

[0032] Preferably, the organic weak acid includes any one or a combination of at least two of lauric acid, myristic acid, palmitic acid and stearic acid;

[0033] Preferably, the pre-crosslinking degree of the high-transmittance EVA layer 1 is 2-10%;

[0034] Preferably, the pre-crosslinking degree of the white EVA layer 2 is 20-30%;

[0035] Preferably, the composite white film is produced by single-screw twin-machine co-extrusion and composite die extrusion, followed by casting, embossing, trimming, winding and irradiation.

[0036] Example 2. The difference between this example and Example 1 is that the flow enhancer is polybutadiene containing double bonds, the molecular weight is 406 g / mol, and the addition amount is 3 parts; the organic weak acid is stearic acid, and the addition amount is 0.2 parts; the thickness of the high-transmittance EVA layer is 100 um, and the pre-crosslinking degree is 5%; the thickness of the white EVA layer is 350 um, and the pre-crosslinking degree is 25%.

[0037] Example 3. The difference between this example and Example 1 is that the flow enhancer is polyisobutylene containing a-terminal double bond, the molecular weight is 560 g / mol, and the addition amount is 1 part; the organic weak acid is lauric acid, and the addition amount is 0.1 part; the thickness of the high-transmittance EVA layer is 50 μm, and the pre-crosslinking degree is 10%; the thickness of the white EVA layer is 400 μm, and the pre-crosslinking degree is 30%.

[0038] Example 4 is different from Example 1 in that: the flow enhancer is 3 parts of double-bond polyisoprene with a molecular weight of 630 g / mol, and 2 parts of double-bond polyisobutylene with a molecular weight of 980 g / mol; the organic weak acid is 0.2 parts of myristic acid and 0.1 parts of palmitic acid; the thickness of the high-transmittance EVA layer is 150 μm, and the pre-crosslinking degree is 2%; the thickness of the white EVA layer is 300 μm, and the pre-crosslinking degree is 25%.

[0039] Comparative Example 1

[0040] This comparative example (such as Figure 2 ) is a conventional single-layer white film, which includes, by mass: 100 parts of EVA resin, 18 parts of EVA masterbatch with 60% titanium dioxide content, 0.65 parts of tert-butyl peroxycarbonate-2-ethylhexyl ester, 0.55 parts of triallyl isocyanurate, 0.85 parts of ethoxylated trimethylolpropane triacrylate, 0.32 parts of γ-methacryloxypropyl trimethoxysilane, 0.3 parts of bis(2,2,6,6,-tetramethyl-4-piperidinyl) sebacate, 0.05 parts of triethylene glycol bis[β-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate]; thickness is 450um; pre-crosslinking is 35%; it is extruded by a single screw single machine and a single die head, and then cast, embossed, trimmed, rolled and irradiated.

[0041] Comparative Example 2

[0042] This comparative example is a common double-layer co-extruded white film. The high-transmittance EVA layer has the same formula as that of Example 1 except that there is no flow enhancer. The white EVA layer has the same formula as that of Example 1 except that there is no organic weak acid. The thickness of the high-transmittance EVA layer is 100um, and the thickness of the white EVA layer is 350um. The overall pre-crosslinking degree is 20%. The film is prepared by single-screw double-machine co-extrusion and composite die extrusion, followed by casting, embossing, trimming, winding and irradiation.

[0043] Table 1 lists the performance test results of different embodiments and comparative examples.

[0044] Table 1 Performance test data of different embodiments and comparative examples

[0045]

[0046]

[0047] Through the comparison of the performance test data of Example 2, Example 3, Example 4, and Comparative Example 1 and Comparative Example 2, it can be seen that the composite white film of the present invention can significantly reduce the hidden crack problem of the battery cell and reduce the risk of outdoor hot spots of the component by reducing the hardness of the film, improving the fluidity of the high-transmittance EVA layer, and better filling the gap between the welding strip and the battery cell; the bonding strength between the composite film and the battery cell is improved by improving the fluidity of the high-transmittance EVA layer, and the peeling strength between the composite film and the backplane is improved by improving the fluidity of the white EVA layer and accelerating the silane hydrolysis reaction rate in the film during component lamination, thereby reducing the risk of delamination of the component outdoors.

Claims

1. A composite white film for reducing the hidden crack rate of a battery cell, characterized in that: It includes a high-transmittance EVA layer and a white EVA layer distributed from top to bottom, among which: The high-transmittance EVA layer comprises, by mass, 100 parts of EVA resin, 1-5 parts of flow enhancer, 0.6 parts of tert-butyl peroxycarbonate-2-ethylhexyl ester, 0.5 parts of triallyl isocyanurate, 0.8 parts of ethoxylated trimethylolpropane triacrylate, 0.3 parts of γ-methacryloxypropyl trimethoxysilane, 0.2 parts of bis(2,2,6,6,-tetramethyl-4-piperidinyl) sebacate, and 0.05 parts of triethylene glycol bis[β-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate]; The white EVA layer comprises, by mass, 100 parts of EVA resin, 18 parts of EVA masterbatch containing 60% titanium dioxide, 0.65 parts of tert-butyl peroxycarbonate-2-ethylhexyl ester, 0.55 parts of triallyl isocyanurate, 0.85 parts of ethoxylated trimethylolpropane triacrylate, 0.32 parts of γ-methacryloxypropyl trimethoxysilane, 0.3 parts of bis(2,2,6,6,-tetramethyl-4-piperidinyl) sebacate, 0.05 parts of triethylene glycol bis[β-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate], and 0.1-0.3 parts of an organic weak acid.

2. The composite white film for reducing the hidden crack rate of a battery cell according to claim 1, characterized in that: The thickness of the high-transmittance EVA layer is 50-150um, and the thickness of the white EVA layer is 300-450um; 3. The composite white film for reducing the hidden crack rate of a battery cell according to claim 1, characterized in that: The flow enhancer is a low molecular weight polyolefin containing double bonds; 4. The composite white film for reducing the hidden crack rate of a battery cell according to claim 3, characterized in that: The low molecular weight polyolefin containing double bonds includes any one or a combination of at least two of polyisobutylene with a-terminal double bond, polyisoprene containing double bonds and polybutadiene containing double bonds; 5. The composite white film for reducing the hidden crack rate of a battery cell according to claim 3, characterized in that: The molecular weight of the low molecular weight polyolefin containing double bonds is 400-1000 g / mol; 6. The composite white film for reducing the hidden crack rate of a battery cell according to claim 1, characterized in that: The organic weak acid includes any one of lauric acid, myristic acid, palmitic acid and stearic acid or a combination of at least two thereof; 7. The composite white film for reducing the hidden crack rate of a battery cell according to claim 1, characterized in that: The pre-crosslinking degree of the high-transmittance EVA layer is 2-10%; 8. The composite white film for reducing the hidden crack rate of a battery cell according to claim 1, characterized in that: The pre-crosslinking degree of the white EVA layer is 20-30%; 9. The composite white film for reducing the hidden crack rate of a battery cell according to claim 1, characterized in that: The composite white film is prepared by co-extrusion of single-screw twin machines and composite die head, and then through casting, embossing, trimming, winding and irradiation.